2021
DOI: 10.1111/dth.15044
|View full text |Cite
|
Sign up to set email alerts
|

Superficial cryotherapy using dimethyl ether and propane mixture versus microneedling in the treatment of alopecia areata: A prospective single‐blinded randomized clinical trial

Abstract: To verify and compare the therapeutic efficacy and safety of superficial cryotherapy using dimethyl ether and propane (DMEP) mixture vs. microneedling in the treatment of mild scalp alopecia areata (AA). In a prospective randomized single‐blinded clinical trial, 80 patients with clinically evident scalp mild AA were randomly assigned into two groups of 40 patients each. Group (1) was treated by superficial cryotherapy using DMEP in three freeze–thaw cycles of 5 s each. Group (2) was treated by microneedling. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
3
6
1
Order By: Relevance
“…of MN sessions Treatment duration Endpoints Effectiveness Adverse events Jadad score Aboeldahab et al. [ 28 ] n = 80 (50 m, 30 f); alopecia areata (AA) Comparison: cryotherapy versus MN Group 1: cryotherapy Group 2: MN MN automated pen, 1.00–2.00 mm needles, session endpoints marked as 4–5 passes longitudinally, vertically, and diagonally 6, once every 2 weeks 12 weeks Hair counts, hair density, Severity of Alopecia Tool (SALT) scores, photographic evaluation, self assessments Yes Hair counts, hair density, SALT scores, photographic evaluation, and self assessments improved in groups 1 and 2; higher changes to SALT scores in group 2 versus 1 No adverse events in group 2 3 Ragab et al. [ 29 ] n = 60 (48 m, 12 f); AA Combination: PRP solution Group 1: PRP injections Group 2: fractional CO 2 laser + PRP topical Group 3: MN + PRP topical MN roller, 1.50 mm needles, session endpoints marked as 4–5 passes longitudinally, vertically, and obliquely until mild erythema noted 3, once monthly 3 months SALT Yes SALT scores improved in groups 1, 2, and 3; no difference in SALT scores across groups No serious events reported; pain higher in group 1 versus group 3 3 Abdallah et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…of MN sessions Treatment duration Endpoints Effectiveness Adverse events Jadad score Aboeldahab et al. [ 28 ] n = 80 (50 m, 30 f); alopecia areata (AA) Comparison: cryotherapy versus MN Group 1: cryotherapy Group 2: MN MN automated pen, 1.00–2.00 mm needles, session endpoints marked as 4–5 passes longitudinally, vertically, and diagonally 6, once every 2 weeks 12 weeks Hair counts, hair density, Severity of Alopecia Tool (SALT) scores, photographic evaluation, self assessments Yes Hair counts, hair density, SALT scores, photographic evaluation, and self assessments improved in groups 1 and 2; higher changes to SALT scores in group 2 versus 1 No adverse events in group 2 3 Ragab et al. [ 29 ] n = 60 (48 m, 12 f); AA Combination: PRP solution Group 1: PRP injections Group 2: fractional CO 2 laser + PRP topical Group 3: MN + PRP topical MN roller, 1.50 mm needles, session endpoints marked as 4–5 passes longitudinally, vertically, and obliquely until mild erythema noted 3, once monthly 3 months SALT Yes SALT scores improved in groups 1, 2, and 3; no difference in SALT scores across groups No serious events reported; pain higher in group 1 versus group 3 3 Abdallah et al.…”
Section: Resultsmentioning
confidence: 99%
“…and Abdallah et al. showed that MN alone increased hair density and improved SALT scores, respectively [ 28 , 30 ]. However, Giorgio et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AASIS has overall more evidence supporting internal consistency and validity, 18 and has recently also shown some trends of improvement in clinical trials of topical interventions, ciclosporin A and a Janus kinase inhibitor. [21][22][23] As we reported previously, 16 AA-QLI did not significantly improve in patients with AA responding to dupilumab treatment, while AASIS was significantly decreased in dupilumab responders, indicating less negative impact of AA on patients' QoL. We therefore aimed to explore further the utility of these questionnaires in patients with AA before and after treatment and to determine the therapeutic response threshold that will most likely improve the reported outcomes of patients with AA.…”
mentioning
confidence: 85%